Respuesta :
Answer:
The growth factor of f(x) is less than the growth factor of g(x).
Step-by-step explanation:
The general form of exponential function is
[tex]h(x)=ab^x[/tex]
Where, a is the initial value and b is the growth factor.
The given function is
[tex]f(x)=4(3)^x[/tex]
The initial value of f(x) is 4 and the growth factor is 3.
From the given table it is noticed that the function g(x) is passing through the points (0,3), (1,12), (2,48).
[tex]3=ab^0[/tex]
[tex]a=3[/tex]
[tex]12=3(b)^1[/tex]
[tex]b=\frac{12}{3}=4[/tex]
[tex]g(x)=3(4)^x[/tex]
The initial value of g(x) is 3 and the growth factor is 4.
Therefore the growth factor of f(x) is less than the growth factor of g(x).
Answer:
f(x) is less than the growth factor of g(x).
Step-by-step explanation: